BOTTOM-UP LEADERSHIP: THE ROLE OF LEADERSHIP IN COMMUNITY EMPOWERMENT - Nadya Anggara Putri; Dwi Putri Yuliani (Media Bina Ilmiah, 2023)
The purpose of this study is to describe in depth the effectiveness of the bottom-up leadership role in directing community empowerment programs in Balaradin Village which have a welfare impact for a better community life. This study uses a qualitative approach, by collecting data through observation, in-depth interviews, and documentation to obtain data and information about the program to be interpreted. This research was conducted in Balaradin Village, Lebaksiu District, Tegal Regency. The theory used is Beni Pekei (2016) regarding effectiveness factors with the characteristics of measuring resources, organizational structure, technology, leadership, and support. The results of this study show that Balaradin Village, Lebaksiu District, is ready to apply the effectiveness factors of community empowerment programs. This is shown by the application of several of these factors in Balaradin Village, it's just that there are still imperfections in several respects such as Human Resources, Technology and Support which support the effectiveness of community empowerment programs. The dimensions that have good readiness are the dimensions of Organizational Structure and Leadership, while the dimensions that still need improvement and improvement are Resources, Technology and Support. Readiness and unpreparedness are assessed from whether the indicators contained in the majority dimension have been met or not.